New technologies for parliaments managing knowledge for sustaining democracy - Mauro Romanelli (Management dynamics in the knowledge economy, 2016)
Parliaments as information and knowledge-based organizations are embracing the Internet and new technologies of information and communication for coping with the crisis of legitimacy relying on citizens feeling disenchanted about politics. Parliaments as democratic institutions engaging citizens use technology for better managing sources of knowledge and information and developing public policies as result of knowledge sharing and dialogue between public institutions and citizens. Parliaments dealing with an increasing complexity of governing tend to introduce new technologies following an information or knowledge approach to achieve legitimacy as credible institutions encouraging an active participation of citizens, for building a sustainable and democratic path promoting active citizenship. Parliaments sustain democracy by managing knowledge and information, structuring the e-parliament between merely providing a channel for citizens having access to information and developing active communication for engendering a dialogue with citizens to be included and exert influence in the policy process by encouraging participatory models driving the search of knowledge for building policies.
2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920